Between a rock and a hard place: exploring the lived experience of disability and climate injustice - Siri Hallstrøm Eriksen; Sarah L. Bell; David Mfitumukiza; Ruth Kjærsti Raanaas; Riya Pankaj Dani; Nadia Delic-Klevstad; Syeda Faseeha Fatima Gilani; Robyn Grøndahl; Victor Kuteesa; Edwige Marty; David Nangosi; Marianne Skolbekken; et al. (Climate and Development, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Cortico-striatal networking deficits associated with advanced HIV disease and cocaine use - Kareem Al-Khalil; Ryan P. Bell; Sheri L. Towe; Syam Gadde; Emma Burke; Christina S. Meade (Journal of NeuroVirology, 2023)

Hyperthermophilic endospores germinate and metabolize organic carbon in sediments heated to 80°C - Emma Bell; Jayne E. Rattray; Kathryn Sloan; Angela Sherry; Giovanni Pilloni; Casey R. J. Hubert (Environmental Microbiology, 2022)
Cold surface sediments host a seedbank of functionally diverse thermophilic bacteria. These thermophiles are present as endospores, which are widely dispersed in aquatic environments. Here, we investigated the functional potential of endospore populations in cold surface sediments heated to 80°C. Microbial production of acetate was observed at 80°C and could be enhanced by supplying additional organic carbon substrates. Comparison of 16S rRNA gene amplicon libraries from 80°C enrichments to sediments heated to lower temperatures (50–70°C) showed that temperature selects for distinct populations of endospore‐forming bacteria. Whereas sulfate‐reducing thermophiles were enriched in 50–70°C incubations, 80°C exceeds their thermal tolerance and selects for hyperthermophilic organotrophic bacteria that are similarly detected in amplicon libraries from sediments heated to 90°C. Genome‐resolved metagenomics revealed novel carbon cycling members of Symbiobacteriales , Thermosediminibacteraceae , Thermanaeromonas and Calditerricola with the genomic potential for the degradation of carbohydrates, sugars, amino acids and nucleotides. Endospores of thermophilic bacteria are deposited on seabed sediments worldwide where they remain dormant as they are buried in the accumulating sediments. Our results suggest that endospore populations could be activated by temperature increases encountered during burial and show the potential for organotrophic metabolic activity contributing to acetate generation in deep hot sediments.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Genetic Connectivity of Seamount Populations of Bluenose Warehou (Hyperoglyphe antarctica) - Stephanie M. Heyworth; James B. Bell; Christopher M. Wade; Geórgenes Cavalcante; Nicholas Robinson; Emma Young; James Glass; David A. Feary (Frontiers in Marine Science, 2021)
Quantifying the level of population connectivity within and between geographically separated single-species deep-water fisheries stocks will be vital for designing effective management plans to preserve such populations. Despite this, stock structure in many fisheries is still poorly described and, at best, subject to precautionary management. Here we use rapidly evolving mitochondrial genes and microsatellite markers to investigate population connectivity patterns in commercially targeted Hyperoglyphe antarctica populations between four seamounts within the Tristan da Cunha Exclusive Economic Zone (EEZ). We find little evidence of population genetic structure between fished populations, with both mtDNA and microsatellite markers showing that there is low genetic population diversity (reflecting substantial gene flow) across the four seamounts. We also find little genetic differentiation between H. antarctica across the wider Southern Hemisphere. Such results support the role for coordinated management of all four populations across the seamounts, and potentially including stocks associated with Australia and New Zealand, with expansion of the fishery clearly having the potential to substantially impact the source of recruits and therefore wider population sustainability.

Steps to diversify priority‐setting research in conservation: reflections on de Gracia 2021 - Tommaso Jucker; Tatsuya Amano; Alexandra Bell; Emma E. Garnett; Jan Laurens Geffert; Miriam K. Guth; Andrew Hacket‐Pain; Sarah H. Luke; Hannah S. Mumby; Matheus Nunes; Tim Rademacher; David C. Rose; et al. (Conservation Biology, 2021)

Sediment cooling triggers germination and sulfate reduction by heat‐resistant thermophilic spore‐forming bacteria - Emma Bell; Angela Sherry; Giovanni Pilloni; Ana Suárez‐Suárez; Margaret A. Cramm; Guillermo Cueto; Ian M. Head; Casey R. J. Hubert (Environmental Microbiology, 2020)
Summary Thermophilic endospores are widespread in cold marine sediments where the temperature is too low to support growth and activity of thermophiles in situ . These endospores are likely expelled from warm subsurface environments and subsequently dispersed by ocean currents. The endospore upper temperature limit for survival is 140°C, which can be tolerated in repeated short exposures, potentially enabling transit through hot crustal fluids. Longer‐term thermal tolerance of endospores, and how long they could persist in an environment hotter than their maximum growth temperature, is less understood. To test whether thermophilic endospores can survive prolonged exposure to high temperatures, sediments were incubated at 80–90°C for 6, 12 or 463 days. Sediments were then cooled by 10–40°C, mimicking the cooling in subsurface oil reservoirs subjected to seawater injection. Cooling the sediments induced sulfate reduction, coinciding with an enrichment of endospore‐forming Clostridia . Different Desulfofundulus , Desulfohalotomaculum , Desulfallas , Desulfotomaculum and Desulfofarcimen demonstrated different thermal tolerances, with some Desulfofundulus strains surviving for >1 year at 80°C. In an oil reservoir context, heat‐resistant endospore‐forming sulfate‐reducing bacteria have a survival advantage if they are introduced to, or are resident in, an oil reservoir normally too hot for germination and growth, explaining observations of reservoir souring following cold seawater injection.

Deep reef fishes in the world’s epicenter of marine biodiversity - Hudson T. Pinheiro; Bart Shepherd; Cristina Castillo; Rene A. Abesamis; Joshua M. Copus; Richard L. Pyle; Brian D. Greene; Richard R. Coleman; Robert K. Whitton; Emma Thillainath; Abner A. Bucol; Matthew Birt; et al. (Coral Reefs, 2019)

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

Elevated success of multispecies bacterial invasions impacts community composition during ecological succession - Damian W. Rivett; Matt L. Jones; Josep Ramoneda; Shorok B. Mombrikotb; Emma Ransome; Thomas Bell (Ecology Letters, 2018)
Successful microbial invasions are determined by a species’ ability to occupy a niche in the new habitat whilst resisting competitive exclusion by the resident community. Despite the recognised importance of biotic factors in determining the invasiveness of microbial communities, the success and impact of multiple concurrent invaders on the resident community has not been examined. Simultaneous invasions might have synergistic effects, for example if resident species need to exhibit divergent phenotypes to compete with the invasive populations. We used three phylogenetically diverse bacterial species to invade two compositionally distinct communities in a controlled, naturalised in vitro system. By initiating the invader introductions at different stages of succession, we could disentangle the relative importance of resident community structure, invader diversity and time pre‐invasion. Our results indicate that multiple invaders increase overall invasion success, but do not alter the successional trajectory of the whole community.

Distribution of thermophilic endospores in a temperate estuary indicate that dispersal history structures sediment microbial communities - Emma Bell; Lynsay I. Blake; Angela Sherry; Ian M. Head; Casey R.J. Hubert (Environmental Microbiology, 2018)
Summary Endospores of thermophilic bacteria are found in cold and temperate sediments where they persist in a dormant state. As inactive endospores that cannot grow at the low ambient temperatures, they are akin to tracer particles in cold sediments, unaffected by factors normally governing microbial biogeography (e.g., selection, drift, mutation). This makes thermophilic endospores ideal model organisms for studying microbial biogeography since their spatial distribution can be directly related to their dispersal history. To assess dispersal histories of estuarine bacteria, thermophilic endospores were enriched from sediments along a freshwater‐to‐marine transect of the River Tyne in high temperature incubations (50°C). Dispersal histories for 75 different taxa indicated that the majority of estuarine endospores were of terrestrial origin; most closely related to bacteria from warm habitats associated with industrial activity. A subset of the taxa detected were marine derived, with close relatives from hot deep marine biosphere habitats. These patterns are consistent with the sources of sediment in the River Tyne being predominantly terrestrial in origin. The results point to microbial communities in estuarine and marine sediments being structured by bi‐directional currents, terrestrial run‐off and industrial effluent as vectors of passive dispersal and immigration.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

The effects of beetroot juice supplementation on indices of muscle damage following eccentric exercise - Tom Clifford; Oliver Bell; Daniel J. West; Glyn Howatson; Emma J. Stevenson (European Journal of Applied Physiology, 2016)

COX2 expression in neuroblastoma increases tumorigenicity but does not affect cell death in response to the COX2 inhibitor celecoxib - Emma Bell; Frida Ponthan; Claire Whitworth; Deborah A. Tweddle; John Lunec; Christopher P. F. Redfern (Clinical & Experimental Metastasis, 2014)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Ecosystem recovery: heathland response to a reduction in nitrogen deposition - SALLY A. POWER; EMMA R. GREEN; CHRIS G. BARKER; J. NIGEL B. BELL; MIKE R. ASHMORE (Global Change Biology, 2006)
Atmospheric deposition of nitrogen is responsible for widespread changes in the structure and function of sensitive seminatural ecosystems. The proposed reduction in emissions of nitrogenous pollutants in Europe under the Gothenburg Protocol raises the question of whether affected ecosystems have the potential to recover to their previous condition and, if so, over what timescale. Since 1998, we have monitored the response of a lowland heathland in southern England following the cessation of a long‐term nitrogen addition experiment, and subsequent management, assessing changes in vegetation growth and chemistry, soil chemistry and the soil microbial community. Persistent effects of earlier nutrient loading on Calluna growth and phenology, and on the abundance of lichens, were apparent up to 8 years after nitrogen additions ceased, indicating the potential for long‐term effects of modest nutrient loading (up to 15.4 kg N ha −1 yr −1 , over 7 years) on heathland ecosystems. The size and activity of the soil microbial community was elevated in former N‐treated plots, 6–8 years after additions ceased, suggesting a prolonged effect on the rate of nutrient cycling. Although habitat management in 1998 reduced nitrogen stores in plant biomass, effects on belowground nitrogen stores were small. Although some parameters (e.g. soil pH) recover pretreatment levels relatively rapidly, others (e.g. vegetation cover and microbial activity) respond much more slowly, indicating that the ecological effects of even small increases in nitrogen deposition will persist for many years after deposition inputs are reduced. Indeed, calculations suggest that the additional soil nitrogen storage associated with 7 years of experimental nitrogen inputs could sustain the observed effects on plant growth and phenology for several decades. Carry over effects on plant phenology and sensitivity to drought suggest that the persistence of vegetation responses to nitrogen deposition should be integrated into long‐term assessments of the impact of global climate change on sensitive ecosystems.